(untitled) (Research, Society and Development, 2022)
Anxiety is a negative feeling and is related to situations that individuals experience in their daily lives. When this anxiety brings excessive worry and harm to individuals’ lives, it becomes a pathology. This study aimed to determine the prevalence of anxiety in nursing students from a higher education institution. This is a descriptive, cross-sectional study with a quantitative approach. The research participants were students regularly enrolled in the Nursing course of a public higher education institution, distributed in 10 classes. The research sample consisted of 50 students. As for the results, four (8%) students were male and 46 (92%) were female, where the predominant age group was 21-30 years old, and more than half of the students practice physical activities occasionally. Regarding the quantity and quality of sleep, it was noted that more than half (56%) sleep only 6h/day, and 54% classify sleep as unsatisfactory, that is, unable to provide adequate physical and mental rest. It was found that 86% of students consider themselves to be anxious people, however only 22% reported using drug treatment for anxiety. When evaluating the presence of different levels of anxiety, through the Beck Inventory, it was found that the majority had Severe Anxiety (32%) and Mild Anxiety (30%). It is concluded that the university and the professors, should look for ways to reduce this load of demands and pressures on students, making the academic experience light and positive without compromising the learning and responsibilities necessary for professional training.